RUMORS OF THE DEATH OF DISPOSITIONAL RESEARCH ARE VASTLY EXAGGERATED - House, Robert J.; Shane, Scott; Herold, David M. (Academy of Management Review, 1996)
In this article we reply to Davis-Blake and Pfeffer's (1989) critique of dispositional research in organizational behavior and their suggestions for what it would take for dispositional research to make a valid contribution to the field. Based on a review of studies of different populations in various settings and the different assessments of dispositional we conclude that the evidence presents a compelling argument for incorporating dispositional theory into explanations of behavior in organizations.